Potential Application of Tea Polyphenols to the Prevention of COVID-19 Infection: Based on the Gut-Lung Axis - Xu, Lei; Ho, Chi-Tang; Liu, Yanan; Wu, Zufang; Zhang, Xin (Frontiers in Nutrition, 2022)
Coronavirus disease 2019 (COVID-19) disrupts the intestinal micro-ecological balance, and patients often develop the intestinal disease. The gut is the largest immune organ in the human body; intestinal microbes can affect the immune function of the lungs through the gut-lung axis. It has been reported that tea polyphenols (TPs) have antiviral and prebiotic activity. In this review, we discussed TPs reduced lung-related diseases through gut-lung axis by inhibiting dysbiosis. In addition, we also highlighted the preventive and therapeutic effects of TPs on COVID-19 complications, further demonstrating the importance of research on TPs for the prevention and treatment of COVID-19 in humans. Based on this understanding, we recommend using TPs to regulate the gut microbiota to prevent or alleviate COVID-19 through the gut-lung axis.